2016
DOI: 10.1021/acs.jpca.6b02410
|View full text |Cite
|
Sign up to set email alerts
|

Hexapole-Oriented Asymmetric-Top Molecules and Their Stereodirectional Photodissociation Dynamics

Abstract: Abstract.Molecular orientation is a fundamental requisite in the study of stereodirected dynamics of collisional and photoinitiated processes. In this last decade, variable hexapolar electric filters have been developed and employed for the rotational-state selection and the alignment of molecules of increasing complexity, for which main difficulties are their mass, their low symmetry and the very dense rotational manifold. In this work, for the first time, a complex molecule such as 2-bromobutane, an asymmetr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

7
2

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 46 publications
1
31
0
Order By: Relevance
“…Similarly, the cleavage energies for the C-Br and C-I bonds hold in gas phases for the more complex photoinitiated dissociation reaction of the analogous bromobutane. 75,76 The same observations hold in solution phase. 72,73,[77][78][79][80] Either Kwok et al 73 and Zheng and Phillips 77 pointed out that CH 2 Br-I, which is observed in cyclohexane, could undergo an intramolecular reorganization to form a second geometrical isomer CH 2 I-Br; see the reaction scheme in Fig.…”
Section: Introductionsupporting
confidence: 59%
“…Similarly, the cleavage energies for the C-Br and C-I bonds hold in gas phases for the more complex photoinitiated dissociation reaction of the analogous bromobutane. 75,76 The same observations hold in solution phase. 72,73,[77][78][79][80] Either Kwok et al 73 and Zheng and Phillips 77 pointed out that CH 2 Br-I, which is observed in cyclohexane, could undergo an intramolecular reorganization to form a second geometrical isomer CH 2 I-Br; see the reaction scheme in Fig.…”
Section: Introductionsupporting
confidence: 59%
“…These vectors have been inferred from the simulated 2D projection of the threedimensional photofragment angular distribution ( Fig. 2b) (details on the vector correlation of the photodissociation of the oriented 2-bromobutane are given in Nakamura et al 21 ).…”
Section: Photodissociationmentioning
confidence: 99%
“…If the backward orientation is endorsed, a biased pulse should be implemented inside the ion lens to reverse the direction. 5 A 308 nm XeCl excimer laser (LPX 200, Lambda Physik) -pumped dye laser (PD 3000, Lambda…”
Section: Experimental Methodsmentioning
confidence: 99%